"I Said Maybe We Should Use a Condom, and Then that Just Went South": Exploring Condomless Sex among Formerly Incarcerated Black Men in New York City, USA. Issue 5 (13th June 2022) - Rowell-Cunsolo, Tawandra L.; Mkuu, Rahma, S.; Bellerose, Meghan; Haile, Rahwa; Wechsberg, Wendee
ABSTRACT: More than 600, 000 incarcerated individuals are released annually in the United States; a large proportion are Black men incarcerated for drug-related offenses, including drug use and possession. Formerly incarcerated Black men report elevated rates of condomless sex and sexually transmitted infections, including human immunodeficiency virus (HIV). The purpose of this study was to explore condom usage among Black men who were formerly incarcerated for drug-related offenses and living in New York City (NYC). Using a semi-structured interview guide, in-depth interviews were conducted with 26 formerly incarcerated Black men. Interviews were audio-recorded, transcribed, and entered into NVivo, then manually coded utilizing thematic analysis methods. The following four themes were identified: partner type and length of the relationship affected condom use; diminished pleasure was a barrier for condom use; challenges with ill-fitting and poor-quality condoms; and the withdrawal method was used as an HIV prevention technique. Our findings suggest that formerly incarcerated Black men are engaging in condomless sex post-incarceration. Greater exposure to prevention messages and targeted interventions with content that includes interpersonal and condom use skill-building, methods to increase pleasurable condom use, information on HIV and STI transmission modes, and access to pre-exposure prophylaxis (PrEP) may be beneficial for this population.